CCL25 chemokine-guided stem cell attraction: an assessment of possible benefits and risks. (4th October 2018) - Spinnen, Jacob; Ringe, Jochen; Sittinger, Michael
Due to its chemoattraction potential on mesenchymal stromal cells of the CCL25/CCR9 axis, local application of CCL25 to severely damaged tissues may be a promising approach for regenerative therapies. Analysis of the given data revealed that CCL25/CCR9 signaling has a crucial role in regulation of an adult immune homeostasis. CCR9 expression variations resulted in dysfunctional immune response in colitis, rheumatoid arthritis and endometriosis. Regarding oncology, different neoplastic tissues exploit CCL25-dependent CCR9 signaling for either local proliferation or migration processes. The CCR9 pathway likely can trigger crosstalk between the Akt and NOTCH pathway and thus participate in the regulation of the neoplastic behavior. In conclusion, the designated application-tissue requires precise molecular analysis of possible CCR9 expression due to its proto-oncogenic characteristics. Lay abstract: The mesenchymal stromal cells are naturally present in the body and are capable of regenerating severely damaged tissues. Chemokines are able to attract these stromal cells to desired locations in the body. Eventually, the chemokine CCL25 could be injected to locally attract these regenerative stromal cells into damaged tissue. This article evaluates the available literature on potential benefits and risks of this therapy. It has been found that this molecule is important in maintaining a normal immune response and can participate in the formation of various inflammatory diseases, as well as in certain types of cancer development processes. It is concluded, that the targeted tissue has to be analyzed on possible direct interactions with CCL25 to exclude possible risks.